Pengembangan Desa Wisata Purwojati Berbasis Lembaga Masyarakat Desa Hutan Di Lewok Mbulu Desa Purwojati Kabupaten Banyumas - Karma Iswasta Eka; Suwarno; Juanita; Tatik Ariyati (JCSE: Journal of Community Service and Empowerment, 2022)
One of the community activities that can increase residents' income is the development of local tourist destinations. Tourism activities, especially local tourism such as tourist villages, can generate significant economic growth. Utilization of local potential as a tourist village will create new jobs initiated by the community, increase the standard of living of the surrounding community, and increase the level of productivity of the local community. One of the local potentials developed into a tourist destination is Purwojati Village, Banyumas Regency. Purwojati village is an area in the southern mountain range, part of the middle bending line, and part of the southern Serayu mountain range. The condition of Purwojati Village is an undulating hilly area occupied by folded sedimentary rocks that extend from 30 m to more than 250 m above sea level. The potential of this village can be developed into a forest-based tourist destination. However, due to poor conditions in terms of tourism carrying capacity, it needs to be equipped with facilities that can attract tourists with the help of outside parties. LPPM UMP as a partner, allocates a budget from the MBKM Grant Program of the Directorate General of Higher Education, RESEARCH, and TECHNOLOGY to develop this tourist village. The service program includes supporting maps, gazebos, and photo spots using hammocks and camping tents. The service team also conducts land conservation and beautifies the area by planting grass and ornamental plants. Meanwhile, for physical facilities, the service team also trains managers in marketing their tourist destinations through the internet and social media by creating websites. The outputs that have been produced from this activity are news in 9 online mass media, IPR location maps, videos on Youtube, Lewok mBulu website page.